ANALYSIS OF STRATEGIC COMMUNICATION DISCOURSE FOR THE ERADICATION OF THE FREE PAPUA ORGANIZATION BY TNI-POLRI OFFICIALS IN ONLINE MEDIA NEWS FRAMING - Madani, Rahmat; Yasya, Wichitra (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The purpose of this article is to find out the Analysis of Strategic Communication Discourse for the Eradication of the Free Papua Organization (OPM) by TNI-POLRI Officials in Online Media News Framing. The theory used is Social Construction with a constructivist approach. Descriptive qualitative research method with analytical analysis referring to online media news texts. The research results show that strategic communication, TNI-POLRI received support from the Chairman of the MPR to carry out operations to eradicate OPM. Murder data in ( CNN Indonesia : 27: 12: 2023) states that the National Police recorded a total of 199 KKB attacks and 146 victims during 2023, while Jonh Roy Purba in detiknews (28/12/ 2022) stated that the Papua Regional Police recorded 90 cases of group crimes Armed criminals (KKB) will be handled throughout 2022. According to Johnson and Scholes (2005), strategy determines the direction and scope of an organization in the long term, and they say that it should determine how resources should be used and configured to meet market and stakeholder needs. Michael Porter, emphasizes the need for strategy to define and communicate an organization's unique position, and says that it must determine the organizational resources, skills, and competencies must be combined to create competitive advantage. Recommendations, further research Security Communication Discourse Analysis of the attitudes of Human Rights Organizations in Indonesia on OPM issues.